Les dimensions internes des comportements en temps de crise : étude de cas entre l'Inde et le Sri Lanka 1983-1990 - Carment, David (Études internationales, 1992)
On July 29 1987, after 20 years of sustained inter-communal conflict and under great political pressure and war weariness, leaders of the government of Sri Lanka signed an Accord with the Indian government which hady at Sri Lanka s request, intervened in Sri Lanka's military and political conflict. The Accord aimed at the cessation of the ethnic conflict in Sri Lanka. Indian involvement in Sri Lanka's domestic affairs signalled a decisional shift among Sri Lanka's leaders from a policy of resolving the conflict by military means to one of seeking political accommodation with the Tamil separatists. However, the presence of the Indian Peace Keeping Force (IPKF) and previous attempts by the Indian government to air drop supplies to Tamil rebels signalled the beginning of international crisis between India and Sri Lanka. This paper traces the events and decisional flow of Sri Lanka s elites from the pre-crisis period ofl983 to crisis abatement in 1990 in an attempt to understand the events and patterns of behaviour that led to an international crisis between Sri Lanka and India and more generally to elucidate the relationship between domestic ethnic conflict and international crisis. This paper argues that Sri Lanka entered into an international crisis precisely because of internal threats to its political integrity engendered by its domestic ethnic conflict. First, the theoretical literature is explored, allowing for a fuller exploration of the linkages between international crisis and ethnic conflict. Second, the perceptions of Sri Lanka's decision-maker s in response to increasing Indian involvement during the pre-crisis and crisis period are assessed. Third an analysis of SriLankan decision-making process is weighed against patterns of coping found in the theoretical literature. Fourth and finally, implications for further research are explored, specifically the role that ethnic conflicts play in triggering international crises and the implications that has for the management of ethnic conflicts by regional hegemons.